Virtues of the People of al-Shām: A Human Analytical Study and Comparative Evaluation with AI Models (ChatGPT and Gemini) - Hifi, Othman Nayef; Dawood, Thamer Abdullah; Amin, Mohd Zohdi Bin Mohd (Journal of Cultural Analysis and Social Change, 2025)
This study aims to examine the virtues of the people of al-Shām through a human analytical lens and compare the findings with those generated by artificial intelligence models. The research adopts an inductive methodology for data collection and analysis, alongside an applied approach to compare human interpretations with the outputs of AI models. The results indicate that the Gemini model demonstrated superior performance in understanding and analyzing religious and cultural texts, offering interpretations that were more accurate and contextually appropriate than those provided by ChatGPT. These findings underscore the importance of advancing AI models capable of effectively engaging with religious and cultural content, while also highlighting the distinctions between human and machine-based analysis.